Oyster mushroom baglog crushing machine to support a circular economy in the Omah Jamur Ungaran - Nur Islahudin; Herwin Suprijono; Rindra Yusianto; Zaenal Arifin; Salsabiila Zaiima Alhakiim; Vivi Normasari (Community Empowerment, 2024)
Omah Jamur Ungaran is one of the businesses engaged in oyster mushroom cultivation, facing challenges with the waste from the oyster mushroom cultivation process. Baglog waste can be crushed using a baglog crusher machine, which separates the growing medium from its packaging. The aim of this community service project is to provide a solution by creating a baglog crusher machine to enhance production capacity and improve the efficiency of the process. This project has resulted in a baglog crusher machine designed to crush baglog waste, which can then be used to produce processed products such as briquettes. The machine is powered by an electric motor, thereby increasing the efficiency of the baglog waste crushing process.